2012
DOI: 10.1007/s11434-012-5192-1
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of ferrite derived from iron oxidizing bacteria

Abstract: The growth characteristics of Sphaerotilus natans and Leptothrix discophora SS-1 (ATCC43182) were first used to fabricate the ferrite and manganese ferrite. The scanning electron microscopy (SEM), energy dispersive X-ray spectrometry (EDS), X-ray diffraction (XRD), and vibrant sample magnetometer (VSM) were used to make clear their morphology microstructure, chemical composition, crystal structure, and magnetostatic characteristic. The result showed that the hollow ferrite fibers were prepared successfully, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
(24 reference statements)
2
2
0
Order By: Relevance
“…related strain BoFeN1 in laboratory biomineralization experiments conducted in a phosphate rich medium. , Secondary oxidation of Fe­(II) by nitrite produced by enzymatic nitrate reduction explains the formation of amorphous Fe­(III)–Fe­(II) phosphate within the periplasm and its growth on the BoFeN1 cells, as well as at distance from the cells, as shown for the biomineralization of ferric oxyhydroxides by the same strain in phosphate poor medium. , In contrast, S. natans has not been recognized to actively oxidize iron although a recent study by Park et al (2014) suggests that this bacterium could couple nitrate reduction with iron oxidation. Nevertheless, various iron oxyhydroxides including ferrihydrite have been shown to be deposited on S. natans sheaths in laboratory experiments, the nature of which depends on the culture conditions . More generally, iron biosorption by S. natans has also been reported for samples from water treatment systems and water streams. In the present study we demonstrated that amorphous iron phosphate can be deposited on S. natans sheaths, upon oxidation of dissolved Fe­(II) in a phosphate rich medium, either in a bacterial suspension or via sorption on a supported biofilm.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…related strain BoFeN1 in laboratory biomineralization experiments conducted in a phosphate rich medium. , Secondary oxidation of Fe­(II) by nitrite produced by enzymatic nitrate reduction explains the formation of amorphous Fe­(III)–Fe­(II) phosphate within the periplasm and its growth on the BoFeN1 cells, as well as at distance from the cells, as shown for the biomineralization of ferric oxyhydroxides by the same strain in phosphate poor medium. , In contrast, S. natans has not been recognized to actively oxidize iron although a recent study by Park et al (2014) suggests that this bacterium could couple nitrate reduction with iron oxidation. Nevertheless, various iron oxyhydroxides including ferrihydrite have been shown to be deposited on S. natans sheaths in laboratory experiments, the nature of which depends on the culture conditions . More generally, iron biosorption by S. natans has also been reported for samples from water treatment systems and water streams. In the present study we demonstrated that amorphous iron phosphate can be deposited on S. natans sheaths, upon oxidation of dissolved Fe­(II) in a phosphate rich medium, either in a bacterial suspension or via sorption on a supported biofilm.…”
Section: Discussionsupporting
confidence: 53%
“…Nevertheless, various iron oxyhydroxides including ferrihydrite have been shown to be deposited on S. natans sheaths in laboratory experiments, the nature of which depends on the culture conditions . More generally, iron biosorption by S. natans has also been reported for samples from water treatment systems and water streams. In the present study we demonstrated that amorphous iron phosphate can be deposited on S. natans sheaths, upon oxidation of dissolved Fe­(II) in a phosphate rich medium, either in a bacterial suspension or via sorption on a supported biofilm. In addition, as detailed in the next section, we show that this amorphous mineral phase has a strong ability to bind uranyl species that are known to be among the most mobile uranium species under oxidizing conditions.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…By illumination, azo dye can generate isomerization reaction between trans and cis, which is reversible and results in the change of the absorption coefficient. [23][24][25][26] This work reports the preparation and the preliminary characterizations of a hybrid material formed by the combination of PS with Congo Red (CR), an acidic pH indicator. The optical properties of CR/PS system are characterized by Fourier transformer infrared (FTIR) and photoluminescence (PL) spectroscopy methods.…”
mentioning
confidence: 99%